Moral Incentives : Experimental Evidence from Repayments of an Islamic Credit Card - Bursztyn, Leonardo; Fiorin, Stefano; Gottlieb, Daniel; Kanz, Martin (World Bank, Washington, DC, 2015)
This paper studies the role of morality in the decision to repay debts. Using a field experiment with a large Islamic bank in Indonesia, the paper finds that moral appeals strongly increase credit card repayments. In this setting, all of the banks late-paying credit card customers receive a basic reminder to repay their debt one day after they miss the payment due date. In addition, two days before the end of a ten-day grace period, clients in a treatment group also receive a text message that cites an Islamic religious text and states that “non-repayment of debts by someone who is able to repay is an injustice.” This message increases the share of customers meeting their minimum payments by nearly 20 percent. By contrast, sending either a simple reminder or an Islamic quote that is unrelated to debt repayment has no effect on the share of customers making the minimum payment. Clients also respond more strongly to this moral appeal than to substantial financial incentives: receiving the religious message increases repayments by more than offering a cash rebate equivalent to 50 percent of the minimum repayment. Finally, the paper finds that removing religious aspects from the quote does not change its effectiveness, suggesting that the moral appeal of the message does not necessarily rely on its religious connotation.